2013
DOI: 10.1103/physrevb.87.155153
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous valence shift of Pr and Tb ions at the spin-state transition in (Pr1yTby)0.7

Abstract: Temperature dependence of the X-ray absorption near-edge structure (XANES) spectra at the Pr L 3 -and Tb L 3 -edges was measured for the (Pr 1−y Tb y ) 0.7 Ca 0.3 CoO 3 system, in which a metalinsulator (MI) and spin-state (SS) transition took place simultaneously at a critical temperature T MI . A small increase in the valence of the terbium ion was found below T MI , besides the enhancement of the praseodymium valence; the trivalent states, which are stable at room temperature, change to a 3+/4+ ionic mixtur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…In the model, the electrons in the upper e g level remain in the condensed phase, contradicting a model of the [high-spin (HS) or intermediate spin (IS)] ↔ low-spin (LS) change of a single Co 3+ site. However, it can explain the experimental data already reported at that time by X-ray absorption near edge structure (XANES) studies [13]- [19]. It is also consistent with the observed expansion of the CoO 6 octahedra below T S .…”
Section: Introductionsupporting
confidence: 90%
“…In the model, the electrons in the upper e g level remain in the condensed phase, contradicting a model of the [high-spin (HS) or intermediate spin (IS)] ↔ low-spin (LS) change of a single Co 3+ site. However, it can explain the experimental data already reported at that time by X-ray absorption near edge structure (XANES) studies [13]- [19]. It is also consistent with the observed expansion of the CoO 6 octahedra below T S .…”
Section: Introductionsupporting
confidence: 90%
“…25 The calculations suggested that the formal cobalt valence would change below T MI from a mixed-valence Co 3.5þ towards a pure Co 3.0þ with a strong preference for the LS state and, concomitantly, the praseodymium valence would increase from Pr 3þ towards Pr 4þ . The theoretical hypothesis about the crucial role of variable praseodymium valence was experimentally supported by the observation of a Schottky peak in the low temperature specific heat of (Pr 1Ày Y y ) 0.7 Ca 0.3 CoO 3 (y ¼ 0.075 and 0.15), 26 by X-ray absorption near-edge structure (XANES) spectra directly at the Pr L 3 -edge, [27][28][29][30] and by small-angle neutron scattering measurements. 31 It is generally desirable to use a single crystal or an epitaxial film for the physical investigation.…”
Section: Introductionmentioning
confidence: 94%
“…Because of the overlap of the fine structure of La L 2 -edge from the substrate with the Pr L 3 -edge from the film, we selected to measure the Pr L 2 -edge XANES spectra, although we usually measured Pr L 3 -edge XANES spectra in the bulk samples. 27,30 The X-ray beam was monochromatized using a Si(111) double-crystal monochromator. The spectra were recorded in the fluorescence mode by 19-ch solid-state detector (SSD) at various temperatures from 300 to 8 K using a cryocooler.…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanide L 3 -edge x-ray absorption near-edge structure (XANES) spectroscopy has been very successful in providing a bulk-sensitive, accurate, and relatively routine method for measuring n f [2,3,4,5,6,7,8]. Unfortunately, this method is not very effective when applied to actinide materials due to a decrease in the energy separation of relevant 5f spectroscopic features (typically 5 eV [9,10] for light actinides and ≈ 10 eV for the lanthanides) and an overall decrease in the intrinsic spectral resolution from the decreased 2p 3/2 core hole lifetime (about 8-10 eV for the light actinides, compared to 3-4 eV for the lanthanides [11]).…”
Section: Introductionmentioning
confidence: 99%